Modern investment theory - Haugen, Robert A. (Prentice Hall, 2001)
Pearson Education) Intended for introductory graduate or intermediate undergraduate classes in investment management. Textbook covering portfolio theory, capital asset pricing, interest rates and bond management, and options and forward and futures. Previous edition: c1997. DLC: Investment analysis.